PENENTUAN RUTE DISTRIBUSI UNTUK MEMINIMALKAN BIAYA TRANSPORTASI MENGGUNAKAN METODE SAVING MATRIX DAN NEAREST INSERT (Studi Kasus PT. Xyz) - Ridwan Hanif; Nancy Oktyajati; Diyah Dwi Nugraheni (LP3M, 2022)
In this era, the development ofptechnology has encouraged many companies to produce creative, innovative products, and strive to generate higher competitive value for their companies. determining the delivery route has several objectives to be achieved, for example to minimize shipping costs and time or distance traveled. The Saving Matrix methodlis a methodlused in determining product distribution routes to the marketinglarea by determininglthe distribution routes that must be passedlandlthe numberloflvehicles basedlon the capacity oflthe vehicle in orderlto obtain the shortest route and minimum transportation costs. PT. XYZ is a company engagedpin the sale of various needs for agriculture such as fertilizers, seeds and chemical drugs for agricultural production where every day must fulfill every order from customers. The purpose oflthis research is the need for a distribution system that can facilitate the delivery of time efficiency, precise in delivery, and provide the fastest route in the delivery of customer orders. Data collection is done by interviewin and observing the company. The data material was taken from October to November 2020. The results oflthe study obtained that the total distance traveled on the new route was 193.4 km and the total transportation cost was Idr.930,000, so that the method used can minimize the distance and costs traveled.